The Effect of Financial Distress Probability, Firm Size and Liquidity on Stock Return of Energy Users Companies in Indonesia - Fachrudin, Khaira Amalia; Ihsan, M. Fikri (International Journal of Energy Economics and Policy, 2021)
Stock return can be one of the representations of a company’s performance in investment. This study aims at investigating the factors determining the stock return of the largest users of energy production of oil, gas and coal classified in the manufacturing companies at Indonesia’s Stock Exchange for the period of 2016-2018. It involved 134 companies classifies as the largest users of energy production of oil, gas and coal classified as the manufacturing entries in IDX that were used as the target of the population and all were selected for the sample of this study. Financial distress probability, firm size, liquidity and price to cash flow from operating activities ratio become independent variables. The result of multiple linear regression indicated that financial distress probability and liquidity influence significantly on the stock return at alpha five percent in this energy user companies. It implies that the companies must continually maintain their financial health and also invest their idle cash in order to generate the return. Keywords: Financial distress probability, liquidity, stock return JEL Classifications: G32, L60, O16 DOI: https://doi.org/10.32479/ijeep.10677